System identification techniques applied to a laboratory scale WEC point absorber (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Control is a necessary and challenging task in maximizing the energy harvesting from WECs.  Tuning controllers using a brute force method can be time consuming and inefficient.  This paper describes a system identification technique for impedance matching used to inform a proportional integral (PI) control methodology implemented on the Lab Upgrade Point Absorber (LUPA) WEC.  Testing at the O.H. Hinsdale Wave Research Laboratory at Oregon State University with LUPA is detailed outlining the identification procedure using multisine bandlimited white noise to generate an intrinsic impedance model of the WEC.  Validation tests are then described applying the resulting control strategy.  Results summarize the average power output for four regular wave cases with a matrix of damping and stiffness values centered on the impedance matching results.  The proposed control methodology and tuning process has the potential to streamline the maximum power generation from WECs.  The paper also gives more insight into the characterization of the LUPA device and will help researchers better take advantage of the open-source experimental model for future research.